9-O-acetyl sialic acid levels identify committed progenitors of plasmacytoid dendritic cells - Netravali, Ilka A (Glycobiology, 2019)
The origins of plasmacytoid dendritic cells (pDCs) have long been controversial and progenitors exclusively committed to this lineage have not been described. We show here that the fate of hematopoietic progenitors is determined in part by their surface levels of 9-O-acetyl sialic acid. Pro-pDCs were identified as lineage negative 9-O-acetyl sialic acid low progenitors that lack myeloid and lymphoid potential but differentiate into pre-pDCs. The latter cells are also lineage negative, 9-O-acetyl sialic acid low cells but are exclusively committed to the pDC lineage. Levels of 9-O-acetyl sialic acid provide a distinct way to define progenitors and thus facilitate the study of hematopoietic differentiation.